Efficient Selective Extraction of Scandium from Red Mud. (19th May 2023) - Ding, Wei; Bao, Shenxu; Zhang, Yimin; Xiao, Junhui
ABSTRACT: The huge reserves of red mud have a significant potential source of scandium. The scandium can be recovered from red mud by direct acid leaching but the extraction yields are generally low, and the leaching efficiency of iron and silicon is higher. Therefore, the highly selective process steps (a combined sulfation-roasting-water leaching process) were studied to extract scandium from red mud, and in order to minimize costs and waste generated. This study focuses on the phase transformation mechanism and leaching behavior of Sc, Na, Al, Fe, Ti, Ca, and Si in the red mud sulfation-roasting-water leaching process. The results show that the maximum Sc leaching efficiency of 91.98% was obtained at optimum conditions: the roasted at 1023 K for 60 min, the ratio of sulfuric acid to red mud of 0.9 mL/g, the leaching temperature is 323 K, the liquid-to-solid ratio of 5 mL/g, and stirred constantly at 200 rpm leach for 2 h. While the leaching efficiencies of Ca, Na, Fe, Al, Si, and Ti are 21.05%, 93.26%, 1.21%, 9.51%, 1.42%, and 0, respectively. The sulfation-roasting-water leaching process proves to be a promising technique and commercially viable process that allows selective extraction of scandium from red mud, which may contribute to provide options for the treatment of red mud produced continuously by the aluminum industry.